ANALISIS KEPENTINGAN CINA MEWUJUDKAN âSOFT BALANCINGâ TERHADAP AMERIKA SERIKAT MELALUI BRICS - , MUHAMMAD GHUFRON MUSTAQIM; , Dr. NUR RACHMAT YULIANTORO, MA(IR). ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research analyses the Chinaâs interest to create soft-balancing against the USA through BRICS. Using the neorealism perspective and the theory of soft balancing, this research found that to some extent BRICSâ role is relevant to the Chinaâs grand strategy of soft balancing. BRICS facilitates China in implementing the strategy of entangling diplomacy, signals of resolve to balance, and economic strengthening. However, in the aspect of territorial denial BRICSâs role is very limited.